Associated Factors with the Implementation of Patient Safety Culture in Hospital - Juanda, Heri; Tahlil, Teuku; Usman, Said (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To identify factors associated (i.e., organizational culture, patient safety regulation, patient safety management quality) with implementing a patient safety culture in hospitals. METHODOLOGY: Quantitative research was used with a cross-sectional approach. All 219 nurses working in inpatient wards of a hospital in Banda Aceh were conveniently included in this study using a non-probability convenience sampling technique with some inclusion and exclusion sample criteria. Data were collected from 18 to 28 April 2024 using the Organizational Culture Assessment Instrument (OCAI), the Karen-personnel instrument for managing the QPSM, the Hospital Survey on Patient Safety for assessing patient safety culture, and a questionnaire comprising questions based on existing literature for evaluating patient safety regulations. Data analysis involved Pearson correlation and multiple linear regression by SPSS 26 for Windows. RESULTS: There was a relationship between organizational culture (p < .0001, r2 = 0.659), patient safety regulation (p < .0001, r2 = 0.423), and quality management of patient safety (p < .0001, r2 = 0.442) and patient safety culture. The results of the multiple linear regression analysis indicated that higher levels of organizational (p < .0001) and regulatory culture (p < .0001) were associated with a higher patient safety culture among nurses in the hospital's nursing wards. CONCLUSION: Implementing a hospital patient safety culture is associated with the organizational and regulatory culture levels. Organizational and Regulatory Culture Hospitals are encouraged to foster a positive organizational culture ensuring a comfortable and secure working environment and providing training opportunities for nurses to enhance patient safety practices.